Development of diagnostic SNP markers and a novel SNP genotyping assay for distinguishing opium poppies. (October 2022) - Chang, Miwha; Kim, Joo-Young; Lee, Haeyong; Lee, Eun-jung; Lee, Won-Hae; Moon, Seohyun; Choe, Sanggil; Choung, Chong Min
Abstract: The opium poppy acts as an important natural pain reliever but is also responsible for increased rates of severe drug abuse and addiction owing to its characteristic psychoactive effect. Non-medical illicit use of the poppy plant is markedly increasing worldwide, thereby highlighting the need for a robust species identification strategy. In this study, we identified SNPs within the region of two universal DNA barcodes, mat K (maturase K) and the trn L- trn F (tRNA-Leu [3′exon]-tRNA-Phe [exon] intergenic spacer, that are forensically applicable for distinguishing opium poppy species based on a genetic analysis of 164 samples of family Papaveraceae obtained from locations spanning Jeolla-do and Jeju Island, Republic of Korea. A comparative analysis of the DNA barcode sequences for two narcotic types of the Papaver species ( Papaver somniferum, Papaver somniferum subs. setigerum ) to eight non-narcotic species revealed three unique nucleotide substitution events. Newly identified SNPs were located at position 255 of mat K and at positions 305 and 306 of trn L- trn F; the narcotic species contained C, A, and T, whereas non-narcotic species contained T, G, and C at these positions. Phylogenetic analysis demonstrated that newly identified SNPs, which we named PsMAT255 and PsLF305/306, could be used to clearly differentiate between the narcotic and non-narcotic types of Papaver species based on the patterns of nucleotide variation. These results indicate that the nucleotide differences between the narcotic and non-narcotic species may influence genetic markers. We, therefore, developed a novel SNP-based allelic genotyping assay using the RT-PCR system that can reliably differentiate the narcotic type of the Papaver species. In summary, our findings suggest that the newly identified species-specific SNPs of both mat K and trn L- trn F can be used as identification markers of narcotic Papaver species. Furthermore, a newly developed TaqMan allelic discrimination assay may be used as a practically applicable diagnostic method to survey several illicit narcotic specimens carrying the type-specific SNP. Highlights: SNP markers were analyzed to differentiate narcotic and non-narcotic Papaver species. The novel SNP genotyping assay discriminated between narcotic types of Papaver species. Identified SNP markers for 133 suspected to be illegal poppy plants were validated.